A New Predictive Index for Osteoporosis in Men under 70 Years of Age: An Index to Identify Male Candidates for Osteoporosis Screening by Bone Mineral Density. (3rd March 2014) - Kim, Lee Oh; Kim, Hyeon-Ju; Kong, Mi Hee
Abstract : Background . Bone mineral density (BMD) screening guidelines for osteoporosis in men seem to have remained unclear. We aimed to set up a predictive index for the osteoporosis(PIO) in men under 70 years of age and present the optimal cutoff value of it, so that clinicians might use it to identify male candidates who benefit from taking the BMD screening. Methods . Adult men under 70 years old who met certain criteria were included. With the determined significant predictors for osteoporosis, we created a new index that presumably best predicts the osteoporosis and compared the predictability of it to other variables. Lastly, the optimal cutoff value of the PIO was calculated. Results . A total of 359 men were included. Age, weight, and current smoking status turned out to be significant predictors for osteoporosis. The PIO was as follows: [age(years) + 10 (for current smoker)]/weight(kg). Compared to other variables, the PIO showed the greatest predictive performance with the optimal cutoff point being 0.87 at which sensitivity and specificity were 71.9% and 70.0%, respectively. Conclusion . A new predictive index appeared to predict the presence of osteoporosis fairly well and thus can be used with its cutoff point to identify men under 70 years of age who need BMD screening.